PHYSICOCHEMICAL AND ANTIMICROBIAL PROPERTIES OF TRANSLUCENT SOAP PREPARED USING ALOE VERA GEL AND ZIZIPHUS JUJUBE LEAF EXTRACT AS ANTIMICROBIAL SOURCE (FUDMA JOURNAL OF SCIENCES, 2021)
In this study, the antimicrobial and physicochemical properties of translucent antimicrobial soap prepared using two medicinal plants, Aloe vera gel and Ziziphus jujube leaf extract   was evaluated. The results of the physicochemical analysis showed the pH (7.52Â±0.02), hardness(1.3 cmÂ±0.02), solubility (0.82 gÂ±0.02) and foamability (6.80 cmÂ±0.03) of the prepared soap and these values were within the acceptable limit  set by WHO/SON which make the prepared soap skin-friendly. Similarly, the antimicrobial screening was carried out on selected Gram-positive and gram-negative bacteria as well as on fungi species using disc diffusion methods and the results showed varying antimicrobial activity at different concentrations ranging from 62.5-500 mg/ml. However, the susceptibility of test bacteria in terms of the zone of inhibition at 500mg/ml of the soap was observed on Staphylococcus lentus (22 mm), Staphylococcus aureus (20mm), Escherichia coli (15 mm), Raoltella ornithinolytica (12mm). The result of antifungal properties was as follows,  Candida albicans (12 mm), Trichophyton rubrum (12 mm), and Aspergillus nigar (10 mm)  at 500 mg/ml concentration. The results when compared to other antimicrobial soap in the market indicate good quality by inhibiting the growth of both Gram-positive, gram-negative bacteria and fungi. The antimicrobial activities exhibited by the soap in this study could be attributed to the presence of phytochemical constituents in the plant extracts, which signify the potential of the soap as an antimicrobial agent. Therefore, these findings confirmed the efficacy of Aloe vera gel and Zizipus jujube extract in traditional medicine.
Keywords: Soap, translucent, Antimicrobial, Aloe vera, Zizipus jujube, susceptibility test